Effect of Dashamooladi Basti in the Short Term Management of Amavata w.s.r. to Rheumatoid Arthritis - Makodiya, Anjali V; Sharma, Akanksha; Shukla, Ram B; Ramani, Hetal (International Research Journal of Ayurveda & Yoga, 2022)
Context: Bad dietary habits and sedentary lifestyles affect Agni. Weakness of Agnileads to formation of Ama.Ama is indigested Aadya Rasa Dhatu. This Ama produces various Amaprodoshaja Vikara. Among these, Amavata is most challenging for physician. In Amavata Ama gets lodged in Kapha Sthanas with the help of vitiated Vyana Vayu. Thus Prakupita Ama and Vata both lodged in Kostha,Ttrika and Sandhi produces Shotha ,Shoola and Stabdhata. Due to their similar mode of presentation, a disease, rheumatoid arthritis can be broadly grouped under the heading Amavata. Aim: To evaluate the role of Dashmooladi Basti in short term management of Amavata w.s.r. to Rheumatoid arthritis. Material and Method:To emphasize the effect of Basti Karma on Amavata, 30 patients having classical sign and Symptoms of Amavata (R.A.)were selected for present study. Dashamooladi Basti was given indose of 240-320 ml (320 ml for 1st day and 240 ml for 2nd& 3rd day) at NatibubhukshitaKala for 3 days to patients. The subjects for the study were patients who were between the age group of 16 and 60 years. Results: Wilcoxon sign rank test was used to access the effect of therapy on subjective criteria of thesis. Statistically highly significant relief was achieved in all the cardinal & some associated features. Functional parameters were observed to be highly significant, highly significant changes were found on ESR and CRP but changes in RA factor were found insignificant. 40.0 % of the patients showed mild improvement and unimproved in rest as an overall effect. Conclusion: Dashamooladi Basti is effective in the management of Amavata. Most of patients had recurrence immediately after omitted treatment, so it can be said that, in Amavata long term treatment is required.